Pengaruh Pemberian Kompres Hangat Dan Aromaterapi Lavender Terhadap Disminore Pada Remaja Putri - fani, Tifani Hadi Tri Wahyuni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Primary dysmenorrhea is menstrual pain without any organic abnormalities, commonly experienced by adolescent girls, which affects daily activities and quality of life. Non-pharmacological treatments such as warm compresses and lavender aromatherapy are considered effective and safe alternatives. This study aimed to analyze the difference in effectiveness between the application of warm compresses and lavender aromatherapy in reducing dysmenorrhea pain among female students at SMA Ummu Rahmah Patumbak. The study used a quasi-experimental design with a pretest-posttest two-group comparison approach. A total of 20 respondents were divided into two treatment groups. Pain levels were measured using the Numeric Rating Scale, and data were analyzed using the Wilcoxon and Mann-Whitney tests. The results showed a significant reduction in pain in both groups (p<0.05), with the average pain score in the warm compress group decreasing from 5.50 to 0.55, and in the lavender aromatherapy group from 5.30 to 0.65. In conclusion, both interventions effectively reduced dysmenorrhea pain, with warm compresses showing greater effectiveness.